2013
DOI: 10.1007/s12155-013-9305-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Rhizome Composition and Overwintering Ability in Perennial Sorghum spp. Using Near-Infrared Spectroscopy (NIRS)

Abstract: Temperately adapted perennial sorghum feedstocks have recently begun to receive increasing interest as candidate energy crops, producing significant biomass and contributing agroecological benefits including increased soil organic carbon, reduced soil erosion, reduced input requirements, and higher net energy return. Rhizomes are the primary morphological feature facilitating overwintering in Sorghum species; however, underlying physiological mechanisms governing rhizome overwintering remain poorly characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Soluble sugars play an important role in the protection of plant cells against damage caused by cold stress by serving as osmoprotectants and nutrients [ 32 , 33 ]. For example, soluble sugar levels have been found to be positively correlated with overwintering in sorghum [ 34 ]. In addition, proline accumulation is closely related to abiotic stress tolerance [ 35 ], and increased proline content has been observed to be accompanied by a rise in the concentration of soluble sugars [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Soluble sugars play an important role in the protection of plant cells against damage caused by cold stress by serving as osmoprotectants and nutrients [ 32 , 33 ]. For example, soluble sugar levels have been found to be positively correlated with overwintering in sorghum [ 34 ]. In addition, proline accumulation is closely related to abiotic stress tolerance [ 35 ], and increased proline content has been observed to be accompanied by a rise in the concentration of soluble sugars [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of perennial sorghum, the longer, branching rhizomes are more prevalent. Washburn et al (2013b) tracked rhizome composition and found that nutrients are assimilated from rhizomes into above ground tissue, such as basal tillers. This observation by Washburn et al (2013b) could partially explain why basal tillers were more prevalent than rhizomederived shoots for our overwintering determination.…”
Section: Overwintering Capacitymentioning
confidence: 99%
“…Washburn et al (2013b) tracked rhizome composition and found that nutrients are assimilated from rhizomes into above ground tissue, such as basal tillers. This observation by Washburn et al (2013b) could partially explain why basal tillers were more prevalent than rhizomederived shoots for our overwintering determination. Because of this information, our research placed an emphasis on basal tiller production when developing a breeding selection protocol as detailed below.…”
Section: Overwintering Capacitymentioning
confidence: 99%
“…Rhizomes and roots are used to store carbohydrates and proteins, which can be translocated and used to form new shoots during regrowth after dormancy. Nonstructural carbohydrates (NSC) stored in rhizome and roots are important for cold tolerance, winter survival, and regeneration and spring regrowth in perennial forage grasses (Bai, Xun, Li, Zhang, & Li, 2010; Carvalho, Asega, & Figueiredo‐Ribeiro, 2007; Harradine, 1980; Washburn et al., 2013; White, 1973). Two types of NSC have been identified as storage carbohydrates in grasses: starch (polymer of glucose, water insoluble) is the primary storage carbohydrate in warm‐season grasses, whereas water‐soluble carbohydrates (WSC) are the primary storage carbohydrate in cool‐season grasses (Chatterton, Harrison, Bennett, & Asay, 1989; Pollock & Cairns, 1991; Smith, 1972).…”
Section: Introductionmentioning
confidence: 99%